Nutritional composition of in-vitro grown fruit bodies of Cordyceps militaris for health and wellness - Pavleen, Kour; Gupta, Moni; Sharma, Manmohan; Gupta, Sachin; Manoj, B.S. (Mushroom Research, 2024)
Cordyceps militaris an edible and medicinal mushroom has been extensively investigated in the past decade. This health food has now gained global attention due to its immense therapeutic and pharmacological benefits. The present study aims at determining the proximate composition of in vitro grown C. militaris fruit bodies. Proximate composition including crude protein, crude fat, crude fiber, total ash, total carbohydrate and moisture content was determined. Total energy value of the fruit bodies and biological efficiency was estimated during the study along with the principle bioactive compounds like cordycepin, adenosine and cordycepic acid. The results showed the carbohydrate content as 60.04±0.07% of dry weight, whereas protein 23.02±0.10% and fibre 11.06±0.04%. The fruit bodies showed 9.24±0.02 mg/g of cordycepin while 1.05±0.03 mg/g adenosine and 14.36 mg/g of cordycepic acid. The results of indicates that in-vitro grown C. militaris fruit bodies holds a good nutritional and therputic potential.